Aurora kinase protein family in Trypanosoma cruzi: Novel role of an AUK-B homologue in kinetoplast replication. - Matías Fassolari; Guillermo D Alonso (Public Library of Science (PLoS), 2019)
Aurora kinases constitute a family of enzymes that play a key role during metazoan cells division, being involved in events like centrosome maturation and division, chromatin condensation, mitotic spindle assembly, control of kinetochore-microtubule attachments, and cytokinesis initiation. In this work, three Aurora kinase homologues were identified in Trypanosoma cruzi (TcAUK1, -2 and -3), a protozoan parasite of the Kinetoplastida Class. The genomic organization of these enzymes was fully analyzed, demonstrating that TcAUK1 is a single-copy gene, TcAUK2 coding sequence is present in two different forms (short and long) and TcAUK3 is a multi-copy gene. The three TcAUK genes are actively expressed in the different life cycle forms of T. cruzi (amastigotes, trypomastigotes and epimastigotes). TcAUK1 showed a changing localization along the cell cycle of the proliferating epimastigote form: at interphase it is located at the extremes of the kinetoplast while in mitosis it is detected at the cell nucleus, in close association with the mitotic spindle. Overexpression of TcAUK1 in epimastigotes leaded to a delay in the G2/M phases of the cell cycle due a retarded beginning of kinetoplast duplication. By immunofluorescence, we found that when it was overexpressed TcAUK1 lost its localization at the extremes of the kinetoplast during interphase, being observed inside the cell nucleus throughout the entire cell cycle. In summary, TcAUK1 appears to be a functional homologue of human Aurora B kinase, as it is related to mitotic spindle assembling and chromosome segregation. Moreover, TcAUK1 also seems to play a role during the initiation of kinetoplast duplication, a novel role described for this protein.